Packing material for power storage device and power storage device using same

By using polypropylene resin and incompatible components in the packaging material of lithium-ion batteries, the problem of damage to the packaging material during roller conveying is solved, uniform pressure application of battery components is achieved, and the battery is improved Work efficiency.

CN119174033APending Publication Date: 2024-12-20TOPPAN HOLDINGS INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380039623.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-01
Filing Date
2023-05-23
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The packaging materials of existing lithium-ion batteries are easily damaged during roller conveying, resulting in the inability of battery components to apply pressure evenly, affecting the working efficiency of the battery.

Method used

An encapsulation material including a base material layer, a barrier layer and a sealing layer are used, wherein the sealing layer is composed of a polypropylene resin and an incompatible component. The incompatible component occupies an area ratio of 10 to 10 in the cross-section of the sealing layer. 50% to relieve stress and improve injury resistance.

Benefits of technology

The material's injury resistance is significantly improved, and it can effectively relieve stress during the roller conveying process, prevent damage to the sealing layer, ensure uniform pressure application of the battery element, and improve the working efficiency of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119174033A_ABST
    Figure CN119174033A_ABST
Patent Text Reader

Abstract

A sealing material for a power storage device according to one aspect of the present disclosure is provided with at least a base material layer, a barrier layer, and a sealing layer in this order, and the sealing layer contains a polypropylene resin (A) and an incompatible component (B) that is incompatible with the polypropylene resin, and when a cross-section of the sealing layer in the TD direction is observed, the cross-section of the sealing layer in the TD direction is larger than the cross-section in the TD direction, the cross-section in the TD direction is smaller than the cross-section in the TD direction. The area ratio (S1) of the incompatible component (B) in the cross section is 10-50%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a packaging material for an electric storage device and an electric storage device using the packaging material for an electric storage device. Background Art

[0002] As a storage device, it is known that there are secondary batteries such as (for example) lithium ion batteries, nickel-metal hydride batteries and lead storage batteries, and electrochemical capacitors such as double-layer capacitors. Due to the miniaturization of portable devices or the limitation of the installation space, it is required that the storage device be further miniaturized, so lithium ion batteries with high energy density have attracted much attention. As the packaging material used for lithium ion batteries, metal cans were used in the past, but multilayer films that are light in weight, high in heat dissipation and can be made at low cost are gradually used.

[0003] A lithium-ion battery using the multilayer film as a packaging material is called a laminated lithium-ion battery. The packaging material covers the battery contents (positive electrode, separator, negative electrode, electrolyte, etc.) to prevent moisture from penetrating into the interior. A laminated lithium-ion battery can be manufactured, for example, by forming a recess in a portion of the packaging material by cold forming, accommodating the battery contents in the recess, and folding back the rest of the packaging material and sealing the edge portion by heat sealing (for example, refer to Patent Document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-101765 Summary of the invention

[0007] Problems to be solved by the invention

[0008] However, as the next generation battery of lithium-ion batteries, research and development of power storage devices called all-solid-state batteries are underway. In order to improve the conductivity of the battery elements of all-solid-state batteries, all-solid-state batteries are operated while applying pressure. In order to operate the battery efficiently, it is necessary to apply pressure uniformly to the battery elements.

[0009] On the other hand, in the manufacturing process of the battery, when the packaging material is conveyed by rollers, the sealing layer may be damaged. If the sealing layer is damaged, it is impossible to apply pressure evenly to the battery element, and the operating efficiency of the battery is reduced. In other words, the packaging material is required to have excellent scratch resistance.

[0010] The present disclosure provides an outer packaging material for an electric storage device having excellent scratch resistance and an electric storage device using the outer packaging material for an electric storage device.

[0011] Means for solving problems

[0012] One aspect of the present disclosure provides a packaging material, which is a packaging material for a storage device and comprises at least a substrate layer, a barrier layer, and a sealing layer in sequence, wherein the sealing layer contains a polypropylene resin (A) and an incompatible component (B) that is incompatible with the polypropylene resin, and when observing a cross-section of the sealing layer along the TD direction, an area ratio S1 of the incompatible component (B) in the cross-section is 10 to 50%.

[0013] The above-mentioned packaging material has excellent scratch resistance. The inventors speculate that the reasons for this effect are as follows. That is, the sealing layer of the above-mentioned packaging material contains a polypropylene resin (A) and an incompatible component (B). As a result, the incompatible component (B) plays a role in alleviating the stress applied to the packaging material. Moreover, in order to relax the stress and ensure scratch resistance, appropriate stress dispersion is required. By making the area ratio S1 more than 10%, the relaxation of the stress caused by the incompatible component (B) becomes sufficient, and the occurrence of damage in the sealing layer is suppressed. In addition, by making the area ratio S1 less than 50%, the stress reaction applied to the packaging material is suppressed to damage the sealing layer. As a result, the packaging material has excellent scratch resistance.

[0014] Generally, as a measure to improve the scratch resistance, there is a method of adding a crystal nucleating agent to the sealing layer to harden the sealing layer. However, in this case, the sealing strength is reduced. The above-mentioned packaging material has excellent scratch resistance even when the sealing layer does not contain a crystal nucleating agent.

[0015] When observing the cross section of the sealing layer along the MD direction, the area ratio S2 of the incompatible component (B) in the cross section can be 10 to 40%. By making the area ratio S2 more than 10%, the relaxation of the stress caused by the incompatible component (B) becomes more sufficient. In addition, by making the area ratio S2 less than 40%, the stress reaction applied to the packaging material is further suppressed to damage the sealing layer. As a result, the damage resistance of the packaging material tends to be more excellent.

[0016] In one embodiment, the ratio S1 / S2 of the area ratio S1 to the area ratio S2 may be greater than 1. Damage to the sealing layer of the packaging material is caused by stress applied from the roller during roller conveyance, and the stress is applied in the TD direction. When S1 / S2 is greater than 1, stress can be more effectively relieved. As a result, the damage resistance of the packaging material tends to be more excellent.

[0017] In one embodiment, the packaging material may further include an adhesive resin layer between the barrier layer and the sealing layer, wherein the adhesive resin layer contains a polypropylene resin (A) and an incompatible component (B) that is incompatible with the polypropylene resin. When the cross section of the adhesive resin layer along the TD direction is observed, the area ratio S3 of the incompatible component (B) in the cross section is 20 to 70%. By making the adhesive resin layer contain the polypropylene resin (A) and the incompatible component (B), the incompatible component (B) plays a role in alleviating the stress applied to the packaging material. Moreover, by making the area ratio S3 greater than 20%, the stress caused by the incompatible component (B) is sufficiently alleviated. In addition, by making the area ratio S3 less than 70%, the stress reaction applied to the packaging material is suppressed from damaging the sealing layer. As a result, the damage resistance of the packaging material tends to be more excellent.

[0018] In one embodiment, when observing the cross section of the adhesive resin layer along the MD direction, the area ratio S4 of the incompatible component (B) in the cross section can be 20 to 60%. By making the area ratio S4 more than 20%, the stress caused by the incompatible component (B) is relieved more fully. In addition, by making the area ratio S4 less than 60%, the stress reaction applied to the packaging material is further suppressed to damage the sealing layer. As a result, the damage resistance of the packaging material tends to be more excellent.

[0019] In one embodiment, the ratio S3 / S4 of the area ratio S3 to the area ratio S4 may be greater than 1. Damage to the sealing layer of the packaging material is caused by stress applied from the roller during roller conveyance, and the stress is applied in the TD direction. When S3 / S4 is greater than 1, stress can be more effectively relieved. As a result, the damage resistance of the packaging material tends to be more excellent.

[0020] In one embodiment, the ratio S3 / S1 of the area ratio S3 to the area ratio S1 may be greater than 1. Since S3 / S1 is greater than 1, the incompatible component (B) (island component) is greater inside (adhesive resin) than at the starting point of stress (sealant side). As a result, the stress is further relaxed and the reaction of the stress is further reduced. Therefore, the damage resistance of the above-mentioned packaging material tends to be more excellent.

[0021] In one embodiment, the sealing layer can be thicker than the adhesive resin layer. As a result, the packaging material is more likely to disperse stress, and the damage resistance of the above packaging material tends to be more excellent. In one embodiment, the incompatible component (B) can include a polyethylene component. As a result, the damage resistance of the above packaging material tends to be more excellent. In one embodiment, the above packaging material can be used for all-solid-state batteries.

[0022] Another aspect of the present disclosure may be an electric storage device including: an electric storage device body and the above-mentioned packaging material accommodating the electric storage device body. In one embodiment, the electric storage device may be an all-solid-state battery.

[0023] Effects of the Invention

[0024] According to the present disclosure, there are provided a packaging material for an electric storage device having excellent scratch resistance and an electric storage device using the packaging material for an electric storage device. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] [ Figure 1 ] Figure 1 is a schematic cross-sectional view of a packaging material according to one embodiment of the present disclosure.

[0026] [ Figure 2 ] Figure 2 1 is a schematic diagram of a cross section along the TD direction of a sealing layer of a packaging material according to an embodiment of the present disclosure.

[0027] [ Figure 3 ] Figure 3 1 is a schematic diagram of a cross section along the MD direction of a sealing layer of a packaging material according to an embodiment of the present disclosure.

[0028] [ Figure 4 ] Figure 4 is a schematic cross-sectional view of a packaging material according to one embodiment of the present disclosure.

[0029] [ Figure 5 ] Figure 5 This is a perspective view of a power storage device according to one embodiment of the present disclosure. DETAILED DESCRIPTION

[0030] Hereinafter, the preferred embodiments of the present disclosure will be described in detail with appropriate reference to the accompanying drawings. It should be noted that in the accompanying drawings, the same or equivalent parts are marked with the same symbols, and repeated descriptions are omitted. In addition, the dimensional ratios of the accompanying drawings are not limited to the ratios shown in the drawings.

[0031] [Electricity storage device packaging materials]

[0032] Figure 1 Schematically shows a cross-sectional view of one embodiment of the packaging material for a power storage device disclosed in the present invention. Figure 1As shown, the packaging material (packaging material for power storage device) 10 of the present embodiment is a laminated body obtained by stacking the following layers: a base layer 11, a first adhesive layer 12a disposed on one side of the base layer 11, a barrier layer 13 disposed on the side of the first adhesive layer 12a opposite to the base layer 11 and having anti-corrosion treatment layers (a first anti-corrosion treatment layer 14a and a second anti-corrosion treatment layer 14b) on both sides, an adhesive resin layer 15 disposed on the side of the barrier layer 13 opposite to the first adhesive layer 12a, and a sealing layer 16 disposed on the side of the adhesive resin layer 15 opposite to the barrier layer 13. Here, the first anti-corrosion treatment layer 14a is disposed on the surface of the barrier layer 13 on the base layer 11 side, and the second anti-corrosion treatment layer 14b is disposed on the surface of the barrier layer 13 on the sealing layer 16 side. In the packaging material 10, the base layer 11 is the outermost layer, and the sealing layer 16 is the innermost layer. That is, the outer packaging material 10 is used with the base material layer 11 facing the outside of the power storage device and the sealing layer 16 facing the inside of the power storage device.

[0033] Hereinafter, each layer constituting the sealing material 10 will be described in detail.

[0034] <Base material layer 11>

[0035] The base material layer 11 plays the following roles: it imparts heat resistance in the sealing process when manufacturing the power storage device, suppresses the generation of pinholes that may be caused during molding and circulation, and can also impart scratch resistance, chemical resistance, insulation, etc., especially in the case of packaging materials for large-scale power storage devices.

[0036] The base material layer 11 is preferably a layer formed of an insulating resin. As the resin, polyester resin, polyamide resin, polyimide resin, polyamide-imide resin, polyetherketone resin, polyphenylene sulfide resin, polyetherimide resin, polysulfone resin, fluororesin, phenolic resin, melamine resin, urethane resin, allyl resin, silicone resin, epoxy resin, furan resin, acetyl cellulose resin, etc. can be used.

[0037] When these resins are applied to the substrate layer 11, they may be in the form of a stretched or unstretched film, or in the form of a coating film. In addition, the substrate layer 11 may be a single layer or a multilayer, and in the case of a multilayer, different resins may be used in combination. If it is a film, a coextruded film or a film laminated via an adhesive may be used. In the case of a coating film, a coating film formed by laminating the required number of times may be used, or a film and a coating film may be combined to form a multilayer.

[0038] Among these resins, polyester resin and polyamide resin are preferred as materials constituting the base material layer 11 because of their excellent moldability. Examples of polyester resins include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of polyamide resins include nylon 6, nylon 6,6, copolymers of nylon 6 and nylon 6,6, nylon 6, nylon 9T, nylon 10, poly(m-xylene adipamide) (MXD6), nylon 11, and nylon 12.

[0039] When these resins are used in the form of films, biaxially stretched films are preferred. As stretching methods for biaxially stretched films, for example, sequential biaxial stretching, tubular biaxial stretching, simultaneous biaxial stretching, etc. can be cited. From the viewpoint of obtaining more excellent deep drawing formability, the biaxially stretched film is preferably a film stretched by tubular biaxial stretching.

[0040] The thickness of the base material layer 11 is preferably 6 to 100 μm, more preferably 10 to 75 μm, and further preferably 10 to 50 μm. When the thickness of the base material layer 11 is 6 μm or more, the pinhole resistance and insulation of the packaging material 10 tend to be improved. When the thickness of the base material layer 11 is 50 μm or less, the total thickness of the packaging material 10 tends to be reduced.

[0041] In addition, the base layer 11 preferably has a melting peak temperature higher than the melting peak temperature of the sealing layer 16. When the sealing layer 16 has a multi-layer structure, the melting peak temperature of the sealing layer 16 refers to the melting peak temperature of the layer with the highest melting peak temperature. By making the base layer 11 have a melting peak temperature higher than the melting peak temperature of the sealing layer 16, it is possible to suppress the appearance from being deteriorated due to the melting of the base layer 11 (outer layer) during heat sealing.

[0042] The melting peak temperature of the substrate layer 11 is preferably above 290°C, more preferably 290-350°C. As resin films that can be used as the substrate layer 11 and have a melting peak temperature within the above range, there can be listed: polyester films such as nylon films and PET films, polyamide films, polyphenylene sulfide films (PPS films), etc. As the substrate layer 11, a commercially available film can be used, and the substrate layer 11 can also be formed by coating (coating and drying of a coating liquid). It should be noted that the substrate layer 11 can be a single-layer structure or a multi-layer structure, and can be formed by coating a thermosetting resin. In addition, the substrate layer 11 can contain various additives (such as flame retardants, slip agents, anti-blocking agents, antioxidants, light stabilizers, tackifiers, etc.).

[0043] The melting peak temperature T of the base material layer 11 11 The melting peak temperature T of the sealing layer 16 16 The difference (T 11 -T16 ) is preferably 20° C. or more. By setting the temperature difference to 20° C. or more, deterioration in the appearance of the packaging material 10 due to heat sealing can be further sufficiently suppressed.

[0044] <First Adhesive Layer 12a>

[0045] The first adhesive layer 12a is a layer that bonds the substrate layer 11 and the barrier layer 13 together. Specifically, for example, the material constituting the first adhesive layer 12a includes: a polyurethane resin formed by allowing a bifunctional or higher-functional isocyanate compound (multifunctional isocyanate compound) to act on a main agent such as a polyester polyol, a polyether polyol, an acrylic polyol, a carbonate polyol, etc. Depending on the functions and performances required of the packaging material 10, the above-mentioned various polyols can be used alone or in combination of two or more. In addition to the above, a material made of an epoxy resin as a main agent and a curing agent can also be used, but it is not limited to this.

[0046] The first adhesive layer 12a is formed using the adhesive composition containing the above-mentioned main agent and curing agent. In addition, various other additives or stabilizers may be blended into the above-mentioned adhesive composition according to the performance required of the adhesive layer.

[0047] The adhesive composition preferably contains at least one polyfunctional isocyanate compound selected from the group consisting of alicyclic isocyanate polymers and isocyanate polymers containing aromatic rings in the molecular structure as a curing agent. As the polyfunctional isocyanate compound, for example, urate bodies of isophorone diisocyanate, adducts of toluene diisocyanate, adducts of hexamethylene diisocyanate, biuret bodies and urate bodies of hexamethylene diisocyanate, biuret bodies and urate bodies of toluene diisocyanate, adducts, biuret bodies and urate bodies of diphenylmethane diisocyanate, and adducts, biuret bodies and urate bodies of xylylene diisocyanate can be listed.

[0048] As a curing agent, an alicyclic isocyanate polymer and an isocyanate polymer containing an aromatic ring in the molecular structure may be used in combination. By using these in combination, the heat resistance tends to be further improved.

[0049] From the viewpoint of further improving heat resistance, the adhesive composition preferably contains at least one polyol selected from the group consisting of polyester polyols, acrylic polyols, and polycarbonate diols. Among them, polyester polyols are more preferred from the viewpoint of further improving heat resistance.

[0050] In the adhesive composition, the ratio (NCO / OH) of the number of isocyanate groups contained in the polyfunctional isocyanate compound to the number of hydroxyl groups contained in the polyol can be 1.5 to 40.0, or 15.0 to 30.0. When the ratio is above 1.5, the curing agents react with each other and easily generate by-products such as urea resins or biuret resins. Since these by-products contain active hydrogen groups, they interact with the polar groups of the adjacent layers, and the interfacial adhesion is improved, so the heat resistance tends to improve. On the other hand, when the above ratio is below 40.0, the lamination strength under room temperature and high temperature environments can be further improved.

[0051] The thickness of the first adhesive layer 12 a is not particularly limited, but is preferably 1 to 10 μm, more preferably 2 to 7 μm, for example, from the viewpoint of obtaining desired adhesive strength, followability, and processability.

[0052] From the viewpoint of ensuring better lamination strength and obtaining better deep drawing formability both at room temperature and at high temperature, the mass per unit area of ​​the first adhesive layer 12a may be 2.0 to 6.0 g / m 2 , can also be 2.5 to 5.0 g / m 2 , can also be 3.0 ~ 4.0g / m 2 .

[0053] <Barrier layer 13>

[0054] The barrier layer 13 has a water vapor barrier property that prevents moisture from penetrating into the interior of the power storage device. In addition, the barrier layer 13 has ductility for deep drawing. As the barrier layer 13, for example, various metal foils such as aluminum, stainless steel, copper, or metal vapor-deposited films, inorganic oxide vapor-deposited films, carbon-containing inorganic oxide vapor-deposited films, and films provided with these vapor-deposited films can be used. As a film provided with a vapor-deposited film, for example, an aluminum vapor-deposited film and an inorganic oxide vapor-deposited film can be used. These can be used alone or in combination of two or more. As the barrier layer 13, from the aspects of mass (specific gravity), moisture resistance, processability and cost, metal foil is preferred, and aluminum foil is more preferred.

[0055] As aluminum foil, from the perspective of being able to impart the desired ductility during molding, it is particularly preferred to use a soft aluminum foil that has been annealed, but in order to further impart pinhole resistance and ductility during molding, it is more preferred to use an iron-containing aluminum foil (aluminum alloy foil). In 100% by mass of aluminum foil, the iron content in the aluminum foil is preferably 0.1 to 9.0% by mass, more preferably 0.5 to 2.0% by mass. By making the iron content 0.1% or more by mass, a packaging material 10 with better pinhole resistance and ductility can be obtained. By making the iron content 9.0% or less by mass, a packaging material 10 with better softness can be obtained. As aluminum foil, untreated aluminum foil can be used, but from the perspective of imparting corrosion resistance, it is preferred to use aluminum foil that has been degreased. When degreasing the aluminum foil, degreasing can be performed only on one side of the aluminum foil, or degreasing can be performed on both sides.

[0056] The thickness of the barrier layer 13 is not particularly limited, but is preferably 9 to 200 μm, more preferably 15 to 100 μm, in consideration of barrier properties, pinhole resistance, and processability.

[0057] <First and second anticorrosion treatment layers 14a, 14b>

[0058] The first and second anti-corrosion treatment layers 14a, 14b are layers provided to prevent corrosion of the metal foil (metal foil layer) and the like constituting the barrier layer 13. In addition, the first anti-corrosion treatment layer 14a serves to improve the adhesion between the barrier layer 13 and the first adhesive layer 12a. In addition, the second anti-corrosion treatment layer 14b serves to improve the adhesion between the barrier layer 13 and the adhesive resin layer 15. The first anti-corrosion treatment layer 14a and the second anti-corrosion treatment layer 14b may be layers of the same composition or layers of different compositions. The first and second anti-corrosion treatment layers 14a, 14b (hereinafter, also referred to as "anti-corrosion treatment layers 14a, 14b") are formed, for example, by degreasing treatment, hydrothermal modification treatment, anodizing treatment, chemical conversion treatment, or a combination of these treatments.

[0059] As degreasing treatment, acid degreasing and alkali degreasing can be listed. As acid degreasing, methods using inorganic acids such as sulfuric acid, nitric acid, hydrochloric acid, and hydrofluoric acid alone, or using a mixed solution thereof, etc. can be listed. In addition, as acid degreasing, by using an acid degreasing agent obtained by dissolving a fluorine-containing compound such as monosodium ammonium difluoride in the above-mentioned inorganic acid, especially when aluminum foil is used for the barrier layer 13, not only the degreasing effect of aluminum is obtained, but also a passive aluminum fluoride can be formed, which is effective in terms of corrosion resistance. As alkali degreasing, methods using sodium hydroxide, etc. can be listed.

[0060] Examples of the hydrothermal modification treatment include a boehmite treatment in which the aluminum foil is immersed in boiling water to which triethanolamine is added. Examples of the anodic oxidation treatment include an alumite treatment.

[0061] As chemical conversion treatment, there are immersion type and coating type. As immersion type chemical conversion treatment, for example, there are chromate treatment, zirconium treatment, titanium treatment, vanadium treatment, molybdenum treatment, calcium phosphate treatment, strontium hydroxide treatment, cerium treatment, ruthenium treatment, or various chemical conversion treatments consisting of mixed phases thereof. On the other hand, as coating type chemical conversion treatment, there is a method of coating a coating agent having anticorrosion performance on the barrier layer 13.

[0062] Among these anti-corrosion treatments, when at least a portion of the anti-corrosion treatment layer is formed by any of hydrothermal modification, anodic oxidation, and chemical conversion treatment, it is preferred to perform the above-mentioned degreasing treatment in advance. It should be noted that when a metal foil that has been subjected to a degreasing treatment such as a metal foil that has undergone an annealing process is used as the barrier layer 13, it is not necessary to perform a degreasing treatment again in the formation of the anti-corrosion treatment layers 14a and 14b.

[0063] The coating agent used for the coating type chemical conversion treatment preferably contains trivalent chromium. In addition, the coating agent may contain at least one polymer selected from the group consisting of cationic polymers and anionic polymers described below.

[0064] In addition, in the above-mentioned treatments, especially in the hydrothermal modification treatment and the anodizing treatment, the surface of the aluminum foil is dissolved by the treatment agent, thereby forming an aluminum compound (boehmite, anodized aluminum) with excellent corrosion resistance. Therefore, from the barrier layer 13 using the aluminum foil to the anti-corrosion treatment layer 14a, 14b, a co-continuous structure is formed, so that the above-mentioned treatment is also included in the definition of the chemical conversion treatment. On the other hand, as described later, the anti-corrosion treatment layers 14a, 14b can also be formed using only a simple coating method that is not included in the definition of the chemical conversion treatment. As an example of this method, there can be cited: a method of using a sol of a rare earth element oxide such as cerium oxide with an average particle size of less than 100nm as a material that has an anti-corrosion effect on aluminum (corrosion inhibitor effect) and is also suitable in terms of the environment. By using this method, even a common coating method can be used to impart an anti-corrosion effect to metal foils such as aluminum foil.

[0065] Examples of the rare earth element oxide sol include sols using various solvents such as water-based, alcohol-based, hydrocarbon-based, ketone-based, ester-based, and ether-based solvents. Among them, water-based sols are preferred.

[0066] In the above rare earth element oxide sol, inorganic acids such as nitric acid, hydrochloric acid, phosphoric acid or their salts, and organic acids such as acetic acid, malic acid, ascorbic acid, and lactic acid are usually used as dispersion stabilizers to stabilize the dispersion. Among these dispersion stabilizers, phosphoric acid is particularly promising because, in the packaging material 10, (1) the dispersion of the sol is stabilized; (2) the adhesion with the barrier layer 13 is improved by the aluminum chelating ability of phosphoric acid; (3) corrosion resistance is imparted by capturing aluminum ions dissolved by the influence of acid or corrosive gas (passive formation); and (4) dehydration condensation of phosphoric acid is easily caused even at low temperatures, thereby improving the cohesion of the anti-corrosion treatment layer (oxide layer) 14a, 14b.

[0067] The anti-corrosion treatment layers 14a and 14b formed by the rare earth element oxide sol are aggregates of inorganic particles, so even after the drying and curing process, the cohesion of the layer itself may be reduced. Therefore, in this case, in order to supplement the cohesion, the anti-corrosion treatment layers 14a and 14b are preferably composited with anionic polymers or cationic polymers.

[0068] The anti-corrosion treatment layers 14a and 14b are not limited to the aforementioned layers. For example, as in the coating type chromate as a known technique, they can also be formed by using a treatment agent formed by combining phosphoric acid and a chromium compound in a resin binder (aminophenol, etc.). If this treatment agent is used, a layer having both anti-corrosion function and tight adhesion can be formed. In addition, although it is necessary to consider the stability of the coating liquid, a coating agent obtained by previously liquefying a rare earth element oxide sol and a polycationic polymer or a polyanionic polymer can be used to form a layer having both anti-corrosion function and tight adhesion.

[0069] Regardless of whether the structure is a multilayer structure or a single layer structure, the mass per unit area of ​​the anticorrosion treatment layers 14a and 14b is preferably 0.005 to 0.200 g / m 2 , more preferably 0.010 to 0.100 g / m 2 If the mass per unit area is 0.005 g / m 2 If the mass per unit area exceeds 0.200 g / m 2 , the anti-corrosion function will not change basically. On the other hand, when using rare earth element oxide sol, when the coating is thick, the curing by the heat during drying becomes insufficient, which may be accompanied by a decrease in cohesion. It should be noted that the thickness of the anti-corrosion treatment layer 14a, 14b can be converted by its specific gravity.

[0070] From the viewpoint of easily maintaining the close adhesion between the sealing layer and the barrier layer, the anti-corrosion treatment layers 14a, 14b may be, for example, in the form of: containing cerium oxide, 1 to 100 parts by mass of phosphoric acid or phosphate relative to 100 parts by mass of the cerium oxide, and a cationic polymer; or in the form of a barrier layer 13 formed by chemical conversion treatment; or in the form of a barrier layer 13 formed by chemical conversion treatment and containing a cationic polymer.

[0071] <Sealing layer 16>

[0072] The sealing layer 16 is a layer that imparts sealing properties to the packaging material 10 by heat sealing, and is a layer that is arranged inside and heat-sealed (heat-welded) when the storage device is assembled. The sealing layer 16 contains a polypropylene resin (A1) (hereinafter also referred to as "(A1) component") and an incompatible component (B1) (hereinafter also referred to as "(B1) component") that is incompatible with the polypropylene resin. Incompatibility (incompatible system) means that the dispersed phase size is dispersed in the (A1) component with a dispersion size of 500 nm or more and less than 20 μm.

[0073] (A1) component is a resin obtained from a polymerized monomer containing propylene. As the (A1) component, homopolypropylene and random polypropylene can be listed, and homopolypropylene is preferred from the viewpoint of heat resistance. As random polypropylene, for example, copolymers of polypropylene and olefins other than polypropylene can be listed. As olefins, for example, ethylene, butene and octene can be listed. Olefins can be used alone or in combination of two or more. (A1) component can be used alone or in combination of two or more.

[0074] The melting point of the component (A1) is preferably 150°C to 175°C, more preferably 160°C to 170°C, from the viewpoint of heat resistance.

[0075] As the (B1) component, for example, polyolefin-based components can be listed. Polyolefin-based components refer to compounds having a structure derived from olefins. As polyolefins, for example, polyethylene-based components, polybutene-based components and polymethylpentene-based components can be listed. From the perspective of stress relaxation ability, polyethylene-based components are preferred. Polyethylene-based components are compounds having a structure derived from ethylene. Polybutene-based components are compounds having a structure derived from butene. Polymethylpentene-based components are compounds having a structure derived from methylpentene. (B1) component can be a resin or an elastomer. As an elastomer, for example, polyolefin-based elastomers with α-olefin as a comonomer can be listed. As the (B1) component, homopolymers, graft copolymers, block copolymers and random copolymers can be listed. At least a part of these copolymers has an incompatible portion with respect to the (A) component. The copolymer can be a copolymer formed by polymerizing two kinds of materials, a terpolymer formed by polymerizing three kinds of materials, or a copolymer formed by polymerizing four or more kinds of materials.

[0076] As polyethylene components, low-density polyethylene resin (LDPE), medium-density polyethylene resin (MDPE), linear low-density polyethylene resin (LLDPE), and ethylene-α-olefin copolymers are preferred. As ethylene-α-olefin copolymers, for example, copolymers of ethylene and propylene, copolymers of ethylene and butene, copolymers of ethylene and methylpentene, and copolymers of ethylene and octene are preferred.

[0077] The content of the structure derived from ethylene in the polyethylene component may be 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more, based on the total amount of the polyethylene component.

[0078] The content of the polyolefin-based component in the component (B1) may be 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more, based on the total amount of the component (B1).

[0079] The total content of the components (A1) and (B1) in the sealing layer 16 may be 70% by mass or more, 80% by mass or more, or 90% by mass or more based on the total amount of the sealing layer.

[0080] The proportion of the component (A1) in the total mass of the components (A1) and (B1) may be, for example, 70 mass % or more, 80 mass % or more, or 90 mass % or less, or 93 mass % or less, 95 mass % or less, or 97 mass % or less.

[0081] Figure 2 Schematic diagram of a cross section of the sealing layer 16 along the TD direction (vertical direction of the mechanical feed direction). Figure 2As shown, the sealing layer 16 has a sea-island structure in which the (A1) component 31 is a sea and the (B1) component 32 is an island. When observing the cross section of the sealing layer 16 along the TD direction, the area ratio S1 of the (B1) component in the cross section is 10% or more, preferably 15% or more, and more preferably 20% or more from the viewpoint that stress relaxation becomes sufficient and scratch resistance is further improved. The area ratio S1 is 50% or less, preferably 40% or less, and more preferably 35% or less from the viewpoint that the sealing layer 16 becomes hard and scratch resistance tends to be further improved.

[0082] Figure 3 Schematic diagram of a cross section of the sealing layer 16 along the MD direction (machine feed direction). In the cross section along the MD direction, the (B1) component 32 extends in the MD direction compared to the cross section along the TD direction. When observing the cross section of the sealing layer 16 along the MD direction, the area ratio S2 of the (B1) component in the cross section is preferably 10% or more from the perspective of further improving the scratch resistance. From the perspective of further improving the scratch resistance, the area ratio S2 is preferably 40% or less, more preferably 30% or less, and further preferably 25% or less.

[0083] From the viewpoint that the scratch resistance tends to be further improved, the ratio S1 / S2 of the area ratio S1 to the area ratio S2 is preferably greater than 1, more preferably greater than 1.1, and further preferably greater than 1.5. From the same viewpoint, S1 / S2 is preferably less than 5.0, more preferably less than 2.5, and further preferably less than 2.0.

[0084] The area ratio S1 and the area ratio S2 can be measured by observing the cross-section along the TD direction and the MD direction using a scanning electron microscope (SEM), binarizing the observed image and calculating the area of ​​the island part and the sea part respectively. Specifically, they can be measured by the method of the embodiment described later.

[0085] The major diameter of the component (B1) in the cross section along the TD direction of the sealing layer can be 0.01 μm or more, preferably 0.03 μm or more, and more preferably 0.05 μm or more, from the perspective of suppressing the reaction of the stress applied to the packaging material and further improving the damage resistance. The major diameter of the component (B1) in the cross section along the TD direction can be 5 μm or less, preferably 4 μm or less, and more preferably 3 μm or less, from the perspective of relieving the stress applied to the packaging material and further improving the damage resistance. The major diameter of the component (B1) in the cross section along the TD direction is measured by observing the cross section with a scanning electron microscope.

[0086] The major diameter of the component (B1) in the cross section along the MD direction of the sealing layer may be 0.2 μm or more, preferably 0.3 μm or more, and more preferably 0.5 μm or more, from the viewpoint of suppressing the reaction of the stress applied to the packaging material and further improving the scratch resistance. The major diameter of the component (B1) in the cross section along the MD direction may be 15 μm or less, preferably 12.5 μm or less, and more preferably 10 μm or less, from the viewpoint of relieving the stress applied to the packaging material and further improving the scratch resistance. The major diameter of the component (B1) in the cross section along the MD direction is measured by observing the cross section with a scanning electron microscope.

[0087] The sealing layer 16 may contain, for example, a slip agent, an anti-blocking agent, an antioxidant, a light stabilizer, a crystal nucleating agent, a flame retardant, etc. as additives. The content of these additives is preferably 5 parts by mass or less based on 100 parts by mass of the total mass of the sealing layer 16.

[0088] The melting peak temperature of the sealing layer 16 varies depending on the application, but in the case of a packaging material for an all-solid-state battery, it is preferably 160 to 280° C. from the viewpoint of improving heat resistance.

[0089] From the viewpoint that the scratch resistance tends to be further improved, the thickness of the sealing layer 16 is preferably thicker than the adhesive resin layer 15. From the same viewpoint, the ratio of the thickness of the sealing layer 16 to the thickness of the adhesive resin layer 15 (the thickness of the sealing layer 16 / the thickness of the adhesive resin layer 15) is preferably 1.1 or more, more preferably 1.5 or more, and from the same viewpoint, it is preferably 10 or less, more preferably 3 or less.

[0090] The total thickness of the sealing layer 16 and the adhesive resin layer 15 may be 15 to 300 μm, and is preferably 25 to 150 μm, and more preferably 50 to 100 μm from the viewpoint of sealing properties and water vapor barrier properties.

[0091] <Adhesive Resin Layer 15>

[0092] The adhesive resin layer 15 contains a polypropylene resin (A2) (hereinafter also referred to as "(A2) component") and an incompatible component (B2) (hereinafter also referred to as "(B2) component") that is incompatible with the polypropylene resin. Incompatibility (incompatible) means that the dispersed phase size is dispersed in the (A2) component with a size of 500 nm or more and less than 20 μm.

[0093] The component (A2) may be the same material as the component (A1), but the adhesive resin layer 15 preferably contains an acid-modified polyolefin resin.

[0094] The acid-modified polyolefin resin may be a polyolefin resin modified by maleic anhydride, carboxylic acid, sulfonic acid, and derivatives thereof. The acid-modified polyolefin resin may be, for example, a graft copolymer, a block copolymer, and a random copolymer. From the viewpoint of adhesion to the barrier layer 13, the acid-modified polyolefin resin is preferably a polyolefin resin graft-modified by maleic anhydride.

[0095] When observing the cross section of the adhesive resin layer 15 along the TD direction, from the viewpoint that the scratch resistance tends to be further improved, the area ratio S3 of the component (B2) in the cross section is preferably 20% or more, more preferably 30% or more, and further preferably 40% or more. From the same viewpoint, the area ratio S3 is preferably 70% or less, more preferably 60% or less, and further preferably 50% or less.

[0096] When observing the cross section of the adhesive resin layer 15 along the MD direction, the area ratio S4 of the component (B2) in the cross section is preferably 20% or more, more preferably 25% or more, from the viewpoint that the scratch resistance tends to be further improved. From the same viewpoint, the area ratio S4 is preferably 60% or less, more preferably 55% or less, and further preferably 50% or less.

[0097] From the viewpoint that scratch resistance tends to be further improved, the ratio S3 / S4 of the area ratio S3 to the area ratio S4 is preferably greater than 1, more preferably 1.1 or more, and further preferably 1.2 or more. From the same viewpoint, S3 / S4 is preferably 5.0 or less, and more preferably 4.0 or less.

[0098] From the viewpoint that scratch resistance tends to be further improved, the ratio S3 / S1 of the area ratio S3 to the area ratio S1 is preferably greater than 1, more preferably 1.1 or more, and further preferably 1.2 or more. From the same viewpoint, S3 / S1 is preferably 6 or less, and more preferably 3 or less.

[0099] The area ratio S3 and the area ratio S4 can be measured by observing the cross-section along the TD direction and the MD direction using a scanning electron microscope (SEM), binarizing the observed image and calculating the area of ​​the island part and the sea part respectively. Specifically, they can be measured by the method of the embodiment described later.

[0100] The major axis of the component (B2) in the cross section along the TD and MD directions of the adhesive resin layer 15 may be the same as the major axis of the component (B1) in the cross section along the TD and MD directions of the sealing layer. The method for measuring the major axis of the component (B2) in the cross section along the TD and MD directions of the adhesive resin layer 15 may be the same as the method for measuring the major axis of the component (B1) in the cross section along the TD and MD directions of the sealing layer.

[0101] If necessary, the adhesive resin layer 15 may contain various additives such as various compatible and incompatible elastomers, flame retardants, slip agents, anti-blocking agents, antioxidants, light stabilizers, crystal nucleating agents, and tackifiers.

[0102] When the packaging material includes an adhesive resin layer 15 and a sealing layer 16 as the packaging material 10, the resin composition for forming each layer can be prepared separately and laminated by a T-die method or an inflation method, or one layer can be laminated by extruding another layer thereon after film-forming, or each layer can be laminated by pasting with an adhesive after being made by a T-die method or an inflation method. As the adhesive used, from the viewpoint of interface adhesion, an adhesive containing acid-modified polypropylene and a curing agent (e.g., isocyanate, etc.) can be used.

[0103] The resin in the adhesive resin layer 15 and the sealing layer 16 can be analyzed by a known analysis method such as IR, NMR, various mass analysis methods, X-ray analysis, Raman spectroscopy, GPC, DSC, and DMA.

[0104] As mentioned above, the preferred embodiment of the packaging material for a power storage device of this embodiment has been described in detail, but the present disclosure is not limited to such specific embodiments, and various modifications and changes can be made within the scope of the gist of the present disclosure described in the claims.

[0105] For example, in Figure 1 , the case where the anti-corrosion treatment layers 14a and 14b are provided on both sides of the barrier layer 13 is shown, but only one of the anti-corrosion treatment layers 14a and 14b may be provided, or no anti-corrosion treatment layer may be provided. Figure 1 Although the case where the first adhesive layer 12a is provided is shown in FIG. 1 , the first adhesive layer 12a may not be provided.

[0106] exist Figure 1 , the sealing layer is a single layer, but the sealing layer may be a multilayer. In this case, the area ratio S1 is a weighted average value obtained by weighting the area ratio of the (B1) component of each layer in the cross section along the TD direction based on the thickness of each layer. The area ratio S2 is a weighted average value obtained by weighting the area ratio of the (B1) component of each layer in the cross section along the MD direction based on the thickness of each layer.

[0107] exist Figure 1 FIG. 1 shows a case where the barrier layer 13 and the sealant layer 16 are laminated using the adhesive resin layer 15, but it is also possible to Figure 4 The barrier layer 13 and the sealant layer 16 are stacked using the second adhesive layer 12b as in the illustrated power storage device packaging material 20. The packaging material preferably includes a second adhesive resin layer because the scratch resistance tends to be further improved.

[0108] <Second Adhesive Layer 12b>

[0109] The second adhesive layer 12b is a layer for bonding the barrier layer 13 and the sealant layer 16. A common adhesive for bonding the barrier layer 13 and the sealant layer 16 can be used for the second adhesive layer 12b.

[0110] When an anti-corrosion treatment layer 14b is provided on the barrier layer 13 and the second anti-corrosion treatment layer 14b has a layer containing at least one polymer selected from the group consisting of the above-mentioned cationic polymers and anionic polymers, the second adhesive layer 12b is preferably a layer containing a compound reactive with the above-mentioned polymer contained in the second anti-corrosion treatment layer 14b (hereinafter also referred to as a "reactive compound").

[0111] For example, when the second anticorrosion treatment layer 14b contains a cationic polymer, the second adhesive layer 12b preferably contains a compound reactive with the cationic polymer. When the second anticorrosion treatment layer 14b contains an anionic polymer, the second adhesive layer 12b preferably contains a compound reactive with the anionic polymer. In addition, when the second anticorrosion treatment layer 14b contains a cationic polymer and an anionic polymer, the second adhesive layer 12b preferably contains a compound reactive with the cationic polymer and a compound reactive with the anionic polymer. However, the second adhesive layer 12b does not necessarily have to contain the above two compounds, and may also contain a compound reactive with both the cationic polymer and the anionic polymer. Here, "reactive" means forming a covalent bond with a cationic polymer or an anionic polymer. In addition, the second adhesive layer 12b may also contain an acid-modified polyolefin resin.

[0112] Examples of the compound reactive with the cationic polymer include at least one compound selected from the group consisting of a polyfunctional isocyanate compound, a glycidyl compound, a compound having a carboxyl group, and a compound having an oxazoline group.

[0113] As these polyfunctional isocyanate compounds, glycidyl compounds, compounds having carboxyl groups, compounds having oxazoline groups, the polyfunctional isocyanate compounds, glycidyl compounds, compounds having carboxyl groups, compounds having oxazoline groups, etc., which are crosslinking agents for forming a crosslinked structure with a cationic polymer, can be cited. Among these, polyfunctional isocyanate compounds are preferred from the viewpoint of high reactivity with a cationic polymer and easy formation of a crosslinked structure.

[0114] As the reactive compound with anionic polymer, at least one compound selected from the group consisting of glycidyl compounds, compounds with oxazoline groups can be listed. As these glycidyl compounds, compounds with oxazoline groups, glycidyl compounds exemplified above, compounds with oxazoline groups etc. can be listed as the cross-linking agent for making cationic polymer form cross-linked structure. Among these, from the high viewpoint of the reactivity with anionic polymer, preferred glycidyl compounds.

[0115] When the second adhesive layer 12b contains an acid-modified polyolefin resin, it is preferred that the reactive compound is also reactive with the acidic group in the acid-modified polyolefin resin (i.e., forms a covalent bond with the acidic group). Thus, the adhesion to the second anticorrosion treatment layer 14b is further improved. In addition, the acid-modified polyolefin resin becomes a cross-linked structure, and the solvent resistance of the packaging material 20 is further improved.

[0116] The content of the reactive compound is preferably an equal amount to 10 times the amount of the acidic group in the acid-modified polyolefin resin. If it is equal or more, the reactive compound fully reacts with the acidic group in the acid-modified polyolefin resin. On the other hand, when it exceeds 10 times the amount, the crosslinking reaction with the acid-modified polyolefin resin reaches full saturation, so there is a concern that unreacted products exist and various performance reductions. Therefore, for example, the content of the reactive compound is preferably 5 to 20 parts by mass (solid content ratio) relative to 100 parts by mass of the acid-modified polyolefin resin.

[0117] The acid-modified polyolefin resin is obtained by introducing an acidic group into a polyolefin resin. Examples of the acidic group include a carboxyl group, a sulfonic acid group, an anhydride group, and the like, and particularly preferably a maleic anhydride group or a (meth) acrylic acid group, etc. As the acid-modified polyolefin resin, for example, the same resin as the modified polyolefin resin used for the sealing layer 16 can be used.

[0118] Various additives such as a flame retardant, a slip agent, an anti-blocking agent, an antioxidant, a light stabilizer, and a tackifier may be blended into the second adhesive layer 12 b .

[0119] From the viewpoint of suppressing the reduction in heat seal strength associated with corrosive gases such as hydrogen sulfide or electrolytes, and from the viewpoint of further suppressing the reduction in insulation properties, the second adhesive layer 12b may contain, for example, an acid-modified polyolefin and at least one curing agent selected from the group consisting of a polyfunctional isocyanate compound, a glycidyl compound, a compound having a carboxyl group, a compound having an oxazoline group, and a carbodiimide compound. It should be noted that examples of the carbodiimide compound include N,N'-di-o-tolylcarbodiimide, N,N'-diphenylcarbodiimide, N,N'-di-2,6-dimethylphenylcarbodiimide, N,N'-bis(2,6-diisopropylphenyl)carbodiimide, N,N'-dioctyldecylcarbodiimide, N-tolyl-N'-cyclohexylcarbodiimide, N,N'-di-2,2-di-tert-butylphenylcarbodiimide, N-tolyl-N'-phenylcarbodiimide, N,N'-di-p-nitrophenylcarbodiimide, N,N'-di-p-aminophenylcarbodiimide, N,N'-di-p-hydroxyphenylcarbodiimide, N,N'-dicyclohexylcarbodiimide, and N,N'-di-p-tolylcarbodiimide.

[0120] In addition, as the adhesive forming the second adhesive layer 12b, for example, a polyurethane adhesive formed by combining polyisocyanate and polyester polyol composed of hydrogenated dimer fatty acid and diol can also be used. As the adhesive, polyurethane resin formed by allowing difunctional or higher isocyanate compounds to act on a main agent such as polyester polyol, polyether polyol, acrylic polyol, carbonate polyol, etc.; or epoxy resin formed by allowing an amine compound to act on a main agent having an epoxy group, etc., are listed, which are preferred from the viewpoint of heat resistance.

[0121] The thickness of the second adhesive layer 12 b is not particularly limited, but is preferably 1 to 10 μm, more preferably 2 to 7 μm, from the viewpoint of obtaining desired adhesive strength and processability.

[0122] [Method for producing packaging material]

[0123] Next, Figure 1 An example of a method for manufacturing the sealing material 10 shown in FIG.

[0124] The manufacturing method of the packaging material 10 of the present embodiment is generally composed of: a process of providing anti-corrosion treatment layers 14a and 14b on the barrier layer 13; a process of bonding the base material layer 11 and the barrier layer 13 together using the first adhesive layer 12a; a process of further laminating an adhesive resin layer 15 and a sealing layer 16 on the surface of the anti-corrosion treatment layer 14b side of the barrier layer 13 to produce a laminate; and a process of performing an aging treatment on the obtained laminate as needed.

[0125] (Step of Laminating Anticorrosion Treatment Layers 14a and 14b on Barrier Layer 13)

[0126] This step is a step of forming the anticorrosion treatment layers 14a and 14b on the barrier layer 13. As described above, the method includes: degreasing the barrier layer 13, hydrothermal modification, anodizing, chemical conversion, or coating with a coating agent having anticorrosion properties.

[0127] In addition, in the case where the anti-corrosion treatment layers 14a and 14b are multiple layers, for example, the coating liquid (coating agent) of the anti-corrosion treatment layer constituting the lower layer side (barrier layer 13 side) can be coated on the barrier layer 13 and baked to form a first layer, and then the coating liquid (coating agent) of the anti-corrosion treatment layer constituting the upper layer side can be coated on the first layer and baked to form a second layer.

[0128] Degreasing treatment can be performed by spraying or dipping. Hydrothermal modification treatment or anodizing treatment can be performed by dipping. Regarding chemical conversion treatment, dipping, spraying, coating, etc. can be appropriately selected and performed according to the type of chemical conversion treatment.

[0129] As a method for applying the coating agent having an anticorrosive property, various methods such as a gravure coating method, a reverse coating method, a roll coating method, and a bar coating method can be used.

[0130] As described above, various treatments can be applied to both sides or one side of the metal foil, but in the case of single-side treatment, the treatment is preferably applied to the side where the sealant layer 16 is laminated. The above treatments can also be applied to the surface of the base layer 11 as required.

[0131] In addition, the coating amount of the coating agent used to form the first layer and the second layer is preferably 0.005 to 0.200 g / m 2 , more preferably 0.010 to 0.100 g / m 2 .

[0132] When drying and curing is required, it can be performed within a range of 60 to 300° C., which is the base material temperature, depending on the drying conditions of the anticorrosion treated layers 14 a and 14 b used.

[0133] (Step of pasting substrate layer 11 and barrier layer 13)

[0134] This step is a step of pasting the barrier layer 13 provided with the anti-corrosion treatment layers 14a and 14b to the base layer 11 via the first adhesive layer 12a. The base layer 11 is pasted on the surface of the barrier layer 13 on the side of the anti-corrosion treatment layer 14a. As a pasting method, dry lamination, solventless lamination, wet lamination or the like can be used to paste the two together using the material constituting the first adhesive layer 12a. The dry coating amount of the first adhesive layer 12a is preferably set at 1 to 10 g / m 2 In the range of 2 to 7 g / m 2 within the range.

[0135] (Step of Laminating Adhesive Resin Layer 15 and Sealing Layer 16)

[0136] This process is a process of forming an adhesive resin layer 15 and a sealing layer 16 on the surface of the barrier layer 13 on the side of the anti-corrosion treatment layer 14b. As a method for this, there can be cited a method of sandwich-laminating the adhesive resin layer 15 and the sealing layer 16 using an extrusion laminator. In addition, lamination can also be performed by a tandem lamination method or a co-extrusion method of extruding the adhesive resin layer 15 and the sealing layer 16. In the formation of the adhesive resin layer 15 and the sealing layer 16, for example, each component can be formulated in a manner that satisfies the above-mentioned composition of the adhesive resin layer 15 and the sealing layer 16. In the formation of the adhesive resin layer 15, a resin composition for forming a sealing layer containing the constituent components of the above-mentioned adhesive resin layer 15 is used. In the formation of the sealing layer 16, a resin composition for forming a sealing layer containing the constituent components of the above-mentioned sealing layer 16 is used.

[0137] Through this process, we can obtain Figure 1 The laminate shown is formed by laminating the following layers in order: base material layer 11 / first adhesive layer 12a / first anticorrosion treatment layer 14a / barrier layer 13 / second anticorrosion treatment layer 14b / adhesive resin layer 15 / sealing layer 16.

[0138] It should be noted that the adhesive resin layer 15 can be laminated by directly extruding the dry mixed material in the above-mentioned material composition using an extrusion laminator. Alternatively, the adhesive resin layer 15 can be laminated by extrude the granulated material by extruding the granulated material using an extrusion laminator after melt mixing in advance using a single-screw extruder, a double-screw extruder, a Brabender mixer or other melt kneading device, and then granulating the granulated material.

[0139] The area ratio S3 and the area ratio S4 in the adhesive resin layer 15 can be appropriately adjusted by changing the blending amount of the component (B2) in the resin composition for forming the adhesive resin layer.

[0140] The sealing layer 16 can be laminated as a constituent of the sealing layer forming resin composition by directly extruding the material dry mixed in the manner of the above-mentioned material combination composition using an extrusion laminating machine. Alternatively, regarding the adhesive resin layer 15 and the sealing layer 16, it is also possible to preliminarily utilize a single-axis extruder, a double-axis extruder, a Brabender mixer and other melt kneading devices to implement melt mixing to obtain a granulated product, and use the granulated product and utilize an extrusion laminating machine to laminate by a series lamination method or a coextrusion method of extruding the adhesive resin layer 15 and the sealing layer 16. In addition, it is also possible to use a sealing layer forming resin composition, pre-make a sealing monofilm as a casting film, and utilize a sandwich lamination method to laminate the film together with the adhesive resin. From the viewpoint of productivity, the formation speed (processing speed) of the adhesive resin layer 15 and the sealing layer 16 can be, for example, more than 80m / minute.

[0141] The area ratio S1 and the area ratio S2 in the sealing layer 16 can be appropriately adjusted by changing the blending amount of the component (B1) in the sealing layer-forming resin composition.

[0142] (Aging treatment process)

[0143] This process is a process of performing an aging (curing) treatment on the laminate. By performing an aging treatment on the laminate, the adhesion between the substrate layer 11 / the first adhesive layer 12a / the first anticorrosion treatment layer 14a / the barrier layer 13, and the adhesion between the barrier layer 13 / the second anticorrosion treatment layer 14b / the second adhesive layer 12b / the sealing layer 16 can be promoted. In addition, by performing an aging treatment on the laminate, the area ratio S2 and the area ratio S4 can be reduced. The aging temperature can be above 80°C, above 100°C, or above 120°C, and can be below 140°C, below 150°C, or below 160°C. The aging time can be above 1 hour, above 2 hours, or above 3 hours, and can be below 24 hours, below 48 hours, or below 72 hours.

[0144] In this way, it is possible to produce Figure 1 The packaging material 10 of the present embodiment is shown.

[0145] Next, Figure 4 An example of a method for manufacturing the sealing material 20 shown in FIG.

[0146] The manufacturing method of the packaging material 20 of the present embodiment is generally configured to include: a step of providing the anti-corrosion treatment layers 14a and 14b on the barrier layer 13; a step of pasting the base material layer 11 and the barrier layer 13 together using the first adhesive layer 12a; a step of pasting the sealing layer 16 on the anti-corrosion treatment layer 14b side of the barrier layer 13 via the second adhesive layer 12b to obtain a laminate; and a step of subjecting the obtained laminate to an aging treatment as required. The steps up to the step of pasting the base material layer 11 and the barrier layer 13 together using the first adhesive layer 12a can be performed in the same manner as the manufacturing method of the packaging material 10 described above. The step of subjecting the obtained laminate to an aging treatment can be performed in the same manner as the manufacturing method of the packaging material 10 described above.

[0147] (Step of Laminating Second Adhesive Layer 12b and Sealing Layer 16)

[0148] This step is a step of attaching the sealant layer 16 to the anticorrosion treated layer 14b side of the barrier layer 13 via the second adhesive layer 12b to obtain a laminated body. Examples of the attaching method include wet processing and dry lamination.

[0149] In the case of a wet process, a solution or dispersion of an adhesive constituting the second adhesive layer 12b is applied to the anti-corrosion treatment layer 14b, and the solvent is removed at a predetermined temperature to dry the film, or a baking process is performed as required after the film is dried. Then, the sealing layer 16 is laminated to manufacture the packaging material 20. As a coating method, various coating methods previously exemplified can be cited. The preferred dry coating amount of the second adhesive layer 12b is the same as that of the first adhesive layer 12a.

[0150] In this case, the sealant layer 16 can be produced, for example, by using a sealant layer-forming resin composition containing the constituent components of the sealant layer 16 and using a melt extruder. From the viewpoint of productivity, the processing speed of the melt extruder can be set to 80 m / min or more.

[0151] The packaging material for a power storage device disclosed in the present invention is suitable for use as a packaging material for power storage devices such as secondary batteries such as lithium-ion batteries, nickel-metal hydride batteries, and lead storage batteries, and electrochemical capacitors such as electric double-layer capacitors. Among them, the packaging material for a power storage device disclosed in the present invention can maintain excellent heat sealing properties even when used in a high-temperature environment after heat sealing, and is therefore suitable as a packaging material for an all-solid-state battery using a solid electrolyte that is intended to be used in such an environment.

[0152] [Electricity storage device]

[0153] Figure 5 FIG. 1 is a perspective view showing an embodiment of a power storage device manufactured using the above-mentioned packaging material. Figure 5As shown in FIG. 1 , the power storage device 50 is configured to include: a battery element (power storage device body) 52 including electrodes, two metal terminals (leads, current output terminals) 53 extending from the electrodes and used to output current from the battery element 52 to the outside, and a packaging material 10 that contains the battery element 52 in an airtight state. The packaging material 10 is the packaging material 10 involved in the above-mentioned present embodiment, and is used as a container for accommodating the battery element 52. In the packaging material 10, the base material layer 11 is the outermost layer, and the sealing layer 16 is the innermost layer. That is, for the packaging material 10, a laminate film is folded in half and the peripheral portions are heat-fused, or two laminate films are overlapped and the peripheral portions are heat-fused, so that the base material layer 11 becomes the outer side of the power storage device 50 and the sealing layer 16 becomes the inner side of the power storage device 50, thereby forming a configuration in which the battery element 52 is contained inside. The metal terminal 53 is sandwiched and sealed by the packaging material 10 that forms a container with the sealing layer 16 as the inner side. The metal terminal 53 may be sandwiched by the sealing material 10 via the tab seal. In addition, in the power storage device 50, the sealing material 20 may be used instead of the sealing material 10.

[0154] The battery element 52 is formed by sandwiching an electrolyte between a positive electrode and a negative electrode. The metal terminal 53 is formed by a part of the current collector extending outside the packaging material 10, and is formed of a metal foil such as copper foil or aluminum foil.

[0155] The power storage device 50 of this embodiment may be an all-solid-state battery. In this case, a solid electrolyte such as a sulfide-based solid electrolyte may be used as the electrolyte of the battery element 52. The power storage device 50 of this embodiment uses the packaging material 10 of this embodiment, so that pressure is uniformly applied to the battery element, thereby tending to improve the working efficiency.

[0156] Example

[0157] Hereinafter, the present disclosure will be described more specifically based on Examples, but the present disclosure is not limited to these Examples.

[0158] [Materials used]

[0159] The materials used in Examples and Comparative Examples are as follows.

[0160] <Base layer (thickness 25 μm)>

[0161] PET: A polyethylene terephthalate film having one surface subjected to a corona treatment was used.

[0162] <1st adhesive layer (mass per unit area 4.0 g / m 2 )>

[0163] An adhesive was used in which polyester polyol (manufactured by Showa Denko Materials Co., Ltd., trade name: TESLAC 2505-63, hydroxyl value: 7 to 11 mgKOH / g) and urate of isophorone diisocyanate (manufactured by Mitsui Chemicals, Inc., trade name: Takenate 600) were blended so as to have an NCO / OH ratio of 20.0, and the mixture was diluted with ethyl acetate to a solid content of 26% by mass.

[0164] <Second adhesive layer (mass per unit area 3.0 g / m 2 )>

[0165] An adhesive was used in which 10 parts by mass (solid content ratio) of a polyisocyanate compound having an isocyanurate structure was blended with respect to 100 parts by mass of an acid-modified polyolefin resin dissolved in toluene.

[0166] <1st Anticorrosion Treatment Layer (Base Layer Side) and 2nd Anticorrosion Treatment Layer (Sealing Layer Side)>

[0167] (CL-1): A "sodium polyphosphate stabilized cerium oxide sol" having a solid content concentration adjusted to 10% by mass using distilled water as a solvent was used. The sodium polyphosphate stabilized cerium oxide sol was obtained by mixing 10 parts by mass of a sodium salt of phosphoric acid with 100 parts by mass of cerium oxide.

[0168] (CL-2): A composition comprising 90% by mass of "polyallylamine (manufactured by Nittobo Co., Ltd.)" whose solid content concentration was adjusted to 5% by mass using distilled water as a solvent and 10% by mass of "polyglycerol polyglycidyl ether (manufactured by Nagase Chemtex Corporation)" was used.

[0169] <Barrier layer (thickness 40 μm)>

[0170] AL: Annealed and degreased soft aluminum foil (Toyo Aluminum KK, "8079 material")

[0171] <Adhesive Resin Layer and Sealing Layer>

[0172] The materials used for the adhesive resin layer and the sealing layer are shown in Table 1 below.

[0173] [Table 1]

[0174]

[0175] [Production of packaging materials]

[0176] (Example 1)

[0177] First, the first and second anticorrosion treatment layers were formed on the barrier layer in the following manner. That is, micro-gravure coating was performed so that the dry coating amount became 70 mg / m 2 (CL-1) was coated on both sides of the barrier layer in a manner of 100°C and baked in a drying unit at 200°C. Then, micro-gravure coating was performed to a dry coating weight of 20 mg / m 2 (CL-2) is applied on the obtained layer in a manner to form a composite layer composed of (CL-1) and (CL-2) as the first and second anti-corrosion treatment layers. The composite layer exhibits anti-corrosion performance by combining the two types of (CL-1) and (CL-2).

[0178] Next, the first anti-corrosion treatment layer side surface of the barrier layer with the anti-corrosion treatment layer and the corona-treated surface of the substrate layer are adhered together by a dry lamination method using a first adhesive (first adhesive layer) to obtain a first laminate. The barrier layer with the anti-corrosion treatment layer and the substrate layer are laminated in the following manner: the coating amount (mass per unit area) after drying is 4.0 g / m 2 The first adhesive was applied on the first anticorrosion treatment layer in a manner, dried at 80° C. for 1 minute, laminated with the base layer, and aged at 80° C. for 120 hours.

[0179] Next, the first laminate is set in the unwinding section of the extrusion laminator. By coextrusion from a T die under the processing conditions of 270°C and 80m / min, an adhesive resin layer and a sealing layer are sequentially laminated on the second anticorrosion treatment layer of the first laminate, thereby obtaining a packaging material (a laminate of substrate layer / first adhesive layer / first anticorrosion treatment layer / barrier layer / second anticorrosion treatment layer / adhesive resin layer / sealing layer). In the lamination of the adhesive resin layer and the sealing layer, various materials shown in Table 2 are dry-mixed in advance and used for the above-mentioned extrusion lamination. The thickness of the adhesive resin layer and the sealing layer is the value shown in Table 3.

[0180] (Examples 2 to 5)

[0181] The first laminate was obtained in the same manner as in Example 1. The second laminate was obtained by laminating an adhesive resin layer and a sealing layer in this order on the second anticorrosion treatment layer of the first laminate in the same manner as in Example 1. The second laminate was aged at the temperature and time shown in Table 2 to obtain a packaging material.

[0182] (Examples 6 to 12, Comparative Examples 1 to 3)

[0183] A sealing material was obtained in the same manner as in Example 1 except that the materials shown in Table 2 were used as the materials of the adhesive resin layer and the sealing layer.

[0184] (Examples 13 and 17)

[0185] A sealing material was obtained in the same manner as in Example 3 except that the materials shown in Table 2 were used as the materials of the adhesive resin layer and the sealing layer.

[0186] (Examples 14 to 16)

[0187] Except having changed the thickness of the adhesive resin layer and the sealing layer as shown in Table 3, it carried out similarly to Example 3, and obtained the sealing material.

[0188] (Example 18)

[0189] The first laminate was obtained in the same manner as in Example 1. Next, the sealing layer shown in Table 2 was pasted on the second anticorrosion treatment layer of the first laminate using the second adhesive (second adhesive layer) by a dry lamination method. The lamination of the first laminate and the sealing layer was performed in the following manner: the adhesive for forming the second adhesive layer was applied to the second anticorrosion treatment layer in such a manner that the thickness after drying became 3 μm, and after drying at 80° C. for 1 minute, it was laminated with the sealing layer and aged at 120° C. for 3 hours. By the above method, a packaging material (laminate of substrate layer / first adhesive layer / first anticorrosion treatment layer / barrier layer / second anticorrosion treatment layer / second adhesive layer / sealing layer) was prepared.

[0190] [Measurement of the Area Ratio of the Incompatible Component (B)]

[0191] (Examples 1 to 18 and Comparative Examples 1 to 3)

[0192] After fixing the encapsulation material obtained in each example with a resin, a cross section of the encapsulation material was cut out by an ultrathin slicer manufactured by Leica. The ethylene-propylene copolymer component of the cross section was stained with ruthenium tetroxide at 70°C for 2 to 4 hours. Platinum was evaporated on the stained cross section. Then, the cross section was observed using a scanning electron microscope (observation magnification: 2000 times), and an image of the layer to be observed was taken. Observe at any three locations of the cross section of the layer to be observed. Cut out any area (10 μm square) from each of the three images. The cut area was binarized into a sea component and an island component by image processing software (ImageJ), and the proportion of the island component was calculated. Specifically, the cut area was converted into an 8-bit (256 grayscale) image, and the grayscale of the threshold value of the sea component and the island component was automatically set to calculate the area ratio of the island component in the area cut out by binarization. The average value of the area ratio at the three locations was taken as the area ratio of the incompatible component (B) in the cross section of the layer to be observed. The observation targets were the cross sections of the sealant layer and the adhesive resin layer along the MD direction and the TD direction.

[0193] [Evaluation of scratch resistance]

[0194] (Examples 1 to 18 and Comparative Examples 1 to 3)

[0195] The packaging material obtained in each example was subjected to a pencil hardness test. Specifically, a pencil hardness tester specified in JIS K 5600 was used to confirm the damage mode of the sealing layer of the packaging material and measure the pencil hardness. The pencil hardness was evaluated according to the following five levels of "S", "A", "B", "C" and "D". The results are shown in Table 3.

[0196] [Evaluation criteria]

[0197] S: Pencil hardness 5H or above

[0198] A: When the pencil hardness is 3H or more and less than 4H

[0199] B: When the pencil hardness is 2H or more and less than 3H

[0200] C: When the pencil hardness is H or higher and less than 2H

[0201] D: Pencil hardness is less than H [Table 2]

[0202]

[0203] [Table 3]

[0204]

[0205] The gist of the present disclosure lies in the following [1] to

[12] .

[0206] [1] A packaging material for a power storage device comprising at least a base layer, a barrier layer, and a sealing layer in this order,

[0207] The sealant layer contains a polypropylene resin (A) and an incompatible component (B) that is incompatible with the polypropylene resin.

[0208] When the cross section of the sealant layer along the TD direction is observed, the area ratio S1 of the incompatible component (B) in the cross section is 10 to 50%.

[0209] [2] The encapsulating material according to [1], wherein when observing a cross section of the sealing layer along the MD direction, an area ratio S2 of the incompatible component (B) in the cross section is 10 to 40%.

[0210] [3] The packaging material according to [2], wherein a ratio S1 / S2 of the area ratio S1 to the area ratio S2 is greater than 1.

[0211] [4] The packaging material according to any one of [1] to [3],

[0212] An adhesive resin layer is provided between the barrier layer and the sealing layer.

[0213] The adhesive resin layer contains a polypropylene resin (A) and an incompatible component (B) that is incompatible with the polypropylene resin.

[0214] When the cross section of the adhesive resin layer along the TD direction is observed, the area ratio S3 of the incompatible component (B) in the cross section is 20 to 70%.

[0215] [5] The packaging material according to [4], wherein when observing a cross section of the adhesive resin layer along the MD direction, an area ratio S4 of the incompatible component (B) in the cross section is 20 to 60%.

[0216] [6] The packaging material according to [5], wherein a ratio S3 / S4 of the area ratio S3 to the area ratio S4 is greater than 1.

[0217] [7] The encapsulating material according to any one of [4] to [6], wherein a ratio S3 / S1 of the area ratio S3 to the area ratio S1 is greater than 1.

[0218] [8] The encapsulating material according to any one of [4] to [7], wherein the sealing layer is thicker than the adhesive resin layer.

[0219] [9] The packaging material according to any one of [1] to [8], wherein the incompatible component (B) comprises a polyethylene component.

[0220]

[10] The packaging material according to any one of [1] to [9], which is for an all-solid-state battery.

[0221]

[11] An electric storage device comprising:

[0222] A power storage device body, and

[0223] The packaging material according to any one of [1] to

[10] for housing a power storage device body.

[0224]

[12] The power storage device according to

[11] , which is an all-solid-state battery.

[0225] Explanation of symbols

[0226] 10, 20 ... packaging material, 11 ... base material layer, 13 ... barrier layer, 15 ... adhesive resin layer, 16 ... sealing layer, 50 ... power storage device.

Claims

1. A packaging material for a power storage device, comprising at least a substrate layer, a barrier layer, and a sealing layer in this order, The sealant layer contains a polypropylene resin (A) and an incompatible component (B) that is incompatible with the polypropylene resin. When observing the cross section of the sealing layer along the TD direction, the area ratio S1 of the incompatible component (B) in the cross section is 10 to 50%. 2 . The packaging material according to claim 1 , wherein when observing the cross section of the sealing layer along the MD direction, the area ratio S2 of the incompatible component (B) in the cross section is 10 to 40%. 3 . The packaging material according to claim 2 , wherein a ratio S1 / S2 of the area ratio S1 to the area ratio S2 is greater than 1. 4 .

4. The packaging material according to any one of claims 1 to 3, An adhesive resin layer is further provided between the barrier layer and the sealing layer. The adhesive resin layer contains a polypropylene resin (A) and an incompatible component (B) that is incompatible with the polypropylene resin. When observing the cross section of the adhesive resin layer along the TD direction, the area ratio S3 of the incompatible component (B) in the cross section is 20 to 70%. 5 . The packaging material according to claim 4 , wherein when observing a cross section of the adhesive resin layer along the MD direction, an area ratio S4 of the incompatible component (B) in the cross section is 20 to 60%. 6 . The packaging material according to claim 5 , wherein a ratio S3 / S4 of the area ratio S3 to the area ratio S4 is greater than 1. 7 . 7 . The packaging material according to claim 4 , wherein a ratio S3 / S1 of the area ratio S3 to the area ratio S1 is greater than 1. 8 . The packaging material according to claim 4 , wherein the sealing layer is thicker than the adhesive resin layer. 9 . The packaging material according to claim 1 , wherein the incompatible component (B) comprises a polyethylene component. 10 . The packaging material according to claim 1 , which is for an all-solid-state battery.

11. An electric storage device comprising: A power storage device body, and The packaging material according to any one of claims 1 to 10 for housing the power storage device body. 12 . The power storage device according to claim 11 , which is an all-solid-state battery.

Citation Information

Patent Citations

  • External facing material for power storage device

    JP2013101765A